Pengaruh Bank Kapasitor Terhadap Keluaran Generator Induksi 1 Fasa Kecepatan Rendah - Prayitno, Budi; , Agus Supardi, S.T., M.T; , Umar, S.T., M.T (2015)
Electrical energy has an important role in improving the quality of life and economic growth in Indonesia. With the increase of population in Indonesia, resulting in the increasing needs of electricity supply. One of the main equipment to be considered in the planning of power generation systems that induction generators used to convert mechanical energy / swivel into electrical energy. The output of the induction generator is strongly influenced by the value of the capacitor bank size. In this study tested the effect of the size of the capacitors are arranged in parallel to the output of low-speed induction generator which includes the value of the voltage, current and frequency. The study begins by installing an induction motor as prime movers coupled with low speed induction generator. After it is installed on the output capacitor bank of the induction generator. Bank of capacitors composed of a number of measuring 4 μF capacitor and 8μF. The number of capacitors in the capacitor bank alone there are 8 pieces that accompanied the switch. Further mounted resistive load such as incandescent lamps 5 Watt, 10 Watt and 15 Watt. Then testing a low speed induction generator in the rotating speed is 730 RPM and 750 RPM. Once it is done measuring the output of low-speed induction generator is voltage, current and frequency. The data was then analyzed. Results of the study showed a low speed induction generator greater the size of the capacitor to the induction generator, the greater the voltage. After reaching a peak voltage value of the voltage will drop and then the voltage rises again, this is due to the characteristics of an induction generator. The same thing happened in the current, while the value of a random frequency. The greater the load, the greater the smaller the value of current and voltage, while the value of random frequency. The larger the capacitor, the lower the rotational speed of the induction generator. At resistive load obtained frequency 49.8 Hz ideal lies in the size of 44 μF capacitor bank in the load 5 Watt and 48 μF capacitor bank size at 10 Watt load with a speed of 750 RPM. For a voltage of 130 Volt biggest lies in the size of 44 μF capacitor bank with a speed of 750 RPM load 5 Watt. While most 0141 Ampere flows lies in the size of 48 μF capacitor bank with a speed of 730 RPM load 15 Watt. Keywords: induction generator, low speed, capacitor banks, voltage, current, frequency.